Методи та інструменти розробки інформаційної системи валідації результатів неформального навчання - Прийма, С.М.; Строкань, О.В.; Рогушина, Ю.В.; Гладун, А.Я.; Мозговенко, А.А. (Проблеми програмування, 2020)
У публікації розглянуті методи та інструменти розробки інформаційної системи на основі комп'ютерних онтологій. Прототипом комп'ютерної онтології виступає онтологія багатомовного класифікатора навичок ESCO. Представлені етапи розробки інформаційної системи валідації результатів неформального навчання. Проаналізовано сучасні методи проектування та розробки застосувань, призначених для функціонування у відкритому середовищі Web. Автори пропонують інноваційний метод створення інформаційної системи, який базується на використанні основних елементів проекту Semantic Web. В роботі наведено опис інструментів, які використані при розробці інформаційної системи валідації результатів неформального навчання, зокрема проаналізована система управління базами даних Neo4j, робота конекторів та запитів SPARQL до даних, розміщених в RDF-сховищі, охарактеризовані засоби створення веб-серверу, виконаний порівняльний аналіз PHP фреймворки Laravel і Symfony для розробки веб-додатку. В публикации рассмотрены методы и инструменты разработки информационной системы на основе компьютерных онтологий. Прототипом компьютерной онтологии выступает онтология многоязычного классификатора навыков ESCO. Представлены этапы разработки информационной системы валидации результатов неформального обучения. Проанализированы современные методы проектирования и разработки приложений, предназначенных для функционирования в открытой среде Web. Авторы предлагают инновационный метод создания информационной системы, основанный на использовании основных элементов проекта Semantic Web. В работе приведено описание инструментов, которые использованы при разработке информационной системы валидации результатов неформального обучения, в частности проанализирована система управления базами данных Neo4j, работа коннекторов и запросов SPARQL к данным, размещенным в RDF-хранилище, охарактеризованы средства создания веб-сервера, выполненный сравнительный анализ PHP фреймворков Laravel и Symfony для разработки веб-приложения. The publication describes methods and tools for development an information system (IS) for acceptance of the non-formal and informal learning results on base of computer ontologies. ESCO ontology of the multilingual skills classifier is used as a prototype of domain ontology that provides knowledge for developed IS. We propose the main stages of development of IS for validation of the results of non-formal learning that include creation of an ontology schema, process of integration of the obtained ontology into the RDF repository, development of application architecture and creation of user interface. The modern approaches to design and development of knowledge-oriented distributed applications intended for functioning in the open Web environment are analyzed, the existing methods and software tools for the presentation and analysis of knowledge and their suitability for solving the task are considered. We propose an innovative method of IS development based on the use of such elements of the Semantic Web project as ontologies, Web services and software agents. The paper describes the tools used in process of development of IS for validation of non-formal learning outcomes. In particular, we analyse Neo4j database management system serving the GraphDB database, the specifics of connectors and SPARQL requests to the data stored in the RDF repository and the tools used for web server creation. Comparison of PHP frameworks for web applications is performed in consideration of task requirements. Functional modeling of IS in order to determine its main functionalities is performed, and the DFD data flow diagrams of system are designed. The benefits of Laravel software are established on base of the analysis of such criteria as security, readiness to installation of plugins and libraries, support for the MVC (Model-View-Controller) concept. User interface is developed to ensure user dialogue with IS. Authers analyse software tools oriented on development of user interface and select React framework that works efficiently with all software tools selected for IS development on the previous stages of analysis.